O direito de ser esquecido: relações democráticas entre viver on e off line - Naganuma, Mathias Yoneda (2015)
The question of which part of the research asks if the Marco Civil da Internet (Law 12,965/14) is configured as an efficient regulatory law to meet the new demands that have emerged in the online life. Crimes have been committed, wounding individual fundamental rights and national sovereignty, although both are guaranteed in our Constitution. Conflicts and new power relations that emerged in the present Internet scenario are the subject of this research, whose objective is to propose a more democratic and fair Internet, built from the critical analysis of some points of the Marco Civil da Internet . The corpus is formed by the recent decision of the European Court of Justice, which recognized the right to be forgotten, and the bills on this topic which currently proceed through the Brazilian Congress. Assuming that Regulatory Laws of Internet adapted to the digital reality are needed to safeguard democracy, and without forgetting the cognitive changes taking place, produced by the hours and hours that we devote to the screens that surround us (Corpomídia Theory, KATZ and GREINER) We adopted as a methodology two research bases: a) data collection, to present the current Internet scenario in Brazil and b) literature review to analyze both the Marco Civil da Internet as the Right to Be Forgotten. In addition to KATZ and GREINER, the theoretical foundation also has LEONARDI, MAYER-SCHÖNBERGER and LESSIG